Perencanaan Laba Dengan Menggunakan Analisis BEP Pada PT INDRILLCO BAKTI DURI - Deva Hamidatun Thoibah Marbun; Hamdani Arifulsyah (Politeknik Caltex Riau, 2021)
This study aims to determine the income planning there is an expected level of profit by using Break Even Point (BEP) analysis. This analysis is one of the short-term profit planning which can help company management in knowing how big the company's income level is, so that the company does not experience profit or loss (break even). The type of research used in this research is descriptive research with a quantitative approach, the data sources used are primary and secondary data with data collection techniques, namely direct interviews with sources, namely the company's finance department and using financial data documents of PT Indrillco Bakti Duri. The results showed that after separating fixed and variable costs, the BEP mix was calculated for the three company work over service projects with the result that the unit BEP in project 1 was 1,380.46 service hours, for project 2 1,365.61 service hours, and for project 3 as many as 1,395.31 hours of service. Meanwhile, the rupiah BEP for project 1 is Rp. 2,690,759,325.44, for project 2 it is Rp. 3,228,941,479.76, and for project 3 it is Rp. 2,635,966,977.12. Keywords: Cost, Revenue, Profit, Break Even Point Analysis, Profit Planning.